Особенности кровоснабжения межпозвонковых дисков у собак - Гавата, Б.В. (Вестник зоологии, 1976)
Circulatory branches grow in the intervertebral discs in the region of the ventrolateral and dorsal edges. Primary vascular elements have a form of protruded capillary loops which enter the fibrous ring. In the fibrous tissue of the intervertebral disc the blood vessels are located in slit-like spaces between the fibrous ring layers. In spaces between fibrous plates the vascular networks are formed by means of anastomoses. Closer to the central zones of the disc the networks become more fine-cellular. In the gelatinous nucleus circulatory branches are not found. Intraorganic vessels of the disc do not penetrate into bodies of vertebrae. The connection between the vessels of the disc and body of a vertebra is realized in the perichondrium region.